2007
DOI: 10.2220/biomedres.28.101
|View full text |Cite
|
Sign up to set email alerts
|

Effects of walking exercise on nocturia in the elderly

Abstract: We investigated whether nocturia in the elderly was improved by walking exercise, which involved walking rapidly for 30 min or more in the evening or night for 8 weeks. A questionnaire related to micturition and exercise, blood pressure, body composition analysis, blood biochemistry tests, and urinalysis were performed before and after 8 weeks of exercise to investigate the effects of walking. Thirty men (71 years old on average) continued the walking exercise for long enough to undergo evaluation. The number … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
22
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 22 publications
0
22
0
Order By: Relevance
“…In addition, studies on healthy community-dwelling older adults found that maintaining an active lifestyle can reduce the risk of developing UI (Bo & Herbert, 2013). For nocturia, there has been limited investigation; however, a small study ( n = 30 men) noted a decrease in symptoms and better sleep associated with a walking program (Sugaya et al, 2007). …”
Section: Discussionmentioning
confidence: 99%
“…In addition, studies on healthy community-dwelling older adults found that maintaining an active lifestyle can reduce the risk of developing UI (Bo & Herbert, 2013). For nocturia, there has been limited investigation; however, a small study ( n = 30 men) noted a decrease in symptoms and better sleep associated with a walking program (Sugaya et al, 2007). …”
Section: Discussionmentioning
confidence: 99%
“…Two previous studies have examined the potential of PA intervention to reduce nocturia. Sugaya et al (38) enroled 47 elderly men in a walking intervention. Among the 30 men who completed assessment, episodes of nocturia and daytime urinary frequency significantly decreased and nighttime sleep was deeper for 67% of subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals who are more physically active have also been found to have lower levels of systemic inflammation (3), which may potentially reduce their risk of BPH-related outcomes. Sugaya et al (38) hypothesized that the association between PA and nocturia could be due to improved (deeper) sleep (21). If this is indeed the mechanism behind the association, PA may not have a significant effect on BPH/LUTS more broadly because it fails to address the other LUTS associated with the condition but does address nocturia associated with sleep disturbance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, treatment of sleep problems is important for improving nocturia. Besides medication, walking for 30 minutes or more in the evening also decreases the number of nocturnal urinations and induces better sleep (15). The main factor related to the influence of walking on nocturia is that sleep becomes deeper, which may increase the arousal threshold bladder volume.…”
Section: Discussionmentioning
confidence: 99%